Enhanced frequency upconversion in Er3+ doped fluoroindate glass due to energy transfer from Tm3+ - Lozano B, W.; De Araújo, Cid B; Messaddeq, Younes [UNESP] (Elsevier, 2002)
Energy transfer processes between Er3+ and Tm3+ were investigated examining the frequency upconversion emissions in a fluoroindate glass pumped at 790 nm. A 60-fold enhancement in the emission at ≈670 nm originating from Er3+ was observed when Tm3+ at concentration of 2% was introduced in a sample containing 2% of Er3+. The results are explained considering the influence of cross-relaxation processes between the active ions. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Doping (additives); Erbium; Frequencies; Positive ions; Relaxation processes; Thulium; Fluoroindate glasses; Glass